Neuroinflammation: The Role of Anthocyanins as Neuroprotectants - Banji, Otilia J.F.; Banji, David; Makeen, Hafiz A.; Alqahtani, Saad S.; Alshahrani, Saeed (Current Neuropharmacology, 2022)
Neuroinflammation is a trigger for several neurodegenerative and neuropsychiatric disorders. Exposure to noxious external stimuli induces homeostatic disturbances resulting in morphological changes in microglia, their activation, and elaboration of pro-inflammatory mediators. This leads to neuroinflammation with the progressive loss of neurons. Nutraceuticals such as anthocyanins are a class of brightly colored bioactive compounds present in fruits and vegetables with purported health benefits. They interfere with the activation of several signaling cascades that have a prominent role in preventing neuroinflammation. More importantly, anthocyanins can cross the blood-brain barrier and are safe. Hence, the current review focuses on the bioavailability of anthocyanins, clinical and in vitro evidence on their role in impeding the activation of transcription factors, modulating the immune milieu within the central nervous system, preventing the activation of microglia, and averting neuroinflammation.
Keywords: oxidative stress